Performance, feed efficiency, feeding behavior, and cortisol concentration of lambs ranked for Residual Feed Intake and Residual Intake and Gain - Sartori, Luiza Vage Coelho; Gurgeira, Danielle Nunes; Crisóstomo, Charleni [UNESP]; de Paz, Claudia Cristina Paro; Ferreira, Josiel; da Costa, Ricardo Lopes Dias (Springer Nature, 2024)
This study aimed to evaluate the performance, feed efficiency, feeding behavior, and cortisol concentrations of lambs ranked into different groups of Residual Feed Intake (RFI) and Residual Intake and Gain (RIG). Forty Santa Inês lambs with a mean initial age of 120 ± 30 days and mean initial (IBW) and final body weight (FBW) of 28.9 ± 3.2 and 43.7 ± 3.9 kg, respectively, were used. The animals were fed at an automatic feed and water station (Intergado®) for 60 days and classified at the end of the experiment as low-RFI/RIG, medium-RFI/RIG, and high-RFI/RIG according to RFI and RIG. Performance, feed efficiency measures, ingestive behavior, temperament, and cortisol concentrations were measured, and Pearson’s correlation analysis was performed to evaluate the relationship between the variables studied. The variables that differed most between RFI groups were dry matter intake, feed conversion, and feed efficiency, with better values in efficient animals (RFI−). Regarding the RGI groups, the average daily gain of animals classified as RIG- was 19.37% lower than that of animals classified as RIG± and 39.28% lower than that of animals classified as RIG+. Only the hourly feeding rate per day (p = 0.04) differed significantly between RFI and RIG classes, while no differences were observed for the ingestive behavior variables or cortisol. The number of visits to the feed bunk (total, with or without intake) showed no correlation with any performance or efficiency measure. Identifying animals ranked into different RFI and RIG classes shows that more efficient animals have a lower feed intake for the same weight gain and spend less time at the feed bunk.
Keywords: Animal selection; Body weight; Correlation; Cortisol; Santa Inês breed; Water intake